A Histological Study of Ovarian Development in the Giant Red Shrimp Aristaeomorpha foliacea (Crustacea: Decapoda: Aristeidae) from the Southern Tyrrhenian Sea (Western Mediterranean) - Anna Perdichizzi; Laura Pirrera; Valeria Micale; Ugo Muglia; Paola Rinelli (The Scientific World Journal)
The reproductive features of the giant red shrimp, Aristaeomorpha foliacea, were investigated in the southern Tyrrhenian sea by experimental trawl sampling. The annual length-frequency distribution showed a multimodal trend in females, ranging between 16 and 67 mm carapace length (CL), and a unimodal trend in males (18–45 mm CL). Mature males occurred in different proportions all year round, while females displayed seasonal maturity (June—September), with a peak in July. Six oocyte developmental stages were identified, the most advanced of which (Pv, postvitellogenic) had never been described before in this species. Ovary development followed a group-synchronous pattern, with the yolked oocyte stock clearly separated from the reservoir of unyolked oocytes, suggesting that A. foliacea is a total spawner, with determinate fecundity. Based upon histological findings, a revision of macroscopic maturity staging employed in Mediterranean bottom trawl surveys (MEDITS) is proposed.